Impacto de la industrialización sobre la contaminación ambiental del Ecuador durante el período 1972-2018 - Lima Espinoza, María Elizabeth (2023)
CO2 emissions worldwide are approximately 36mm kilotons. In this sense, the aim of the present research is to examine the impact of industrialization on environmental pollution in Ecuador during the period 1972-2018. For this study, the World Bank database (2020) was used. In the methodology, the OLS model was used to test the EKC, the VAR AND VEC models to estimate the long-run and short-run relationship and the Granger cointegration test to evidence the causal nexus. Under this context, among the main results, we found a positive and statistically significant impact of industrialization on CO2 emissions and the EKC is not fulfilled for Ecuador; a short- and long-term relationship between industrialization, CO2 emissions, urbanization, exports, and natural resource rent; as well as a unidirectional causal relationship that goes from industrialization to CO2 emissions. Given these results, the policy implications turn to a main axis such as the change of the productive matrix, to sustain a much more sustainable and environmentally friendly economic growth